Oxford urdu ka guldasta Gul-e-Lala grade 5 - Farooqui, Fozia Ahsan (Karachi : Oxford university press, 2023)
"Oxford Urdu Ka Guldasta Gul-e-Lala (Grade 5)" is a collection of stories, poems, and rhymes aimed at enhancing the Urdu language skills of fifth-grade students. The book features a range of engaging and thought-provoking content that helps improve vocabulary, comprehension, and writing skills. Through its interesting stories and vibrant illustrations, it also introduces students to deeper moral lessons and cultural values. The book is designed to make learning Urdu enjoyable and meaningful, encouraging students to develop a strong foundation in the language while fostering a love for reading.
Keywords: Urdu : Textbook